Meningkatkan Loyalitas Merek Ramah Lingkungan: Peran Konsep Diri, Altruisme, dan Pengetahuan (Enhancing Green Brand Loyalty: The Role of Self-Concept, Altruism, and Knowledge) - Putra, Setiawan Mandala; Farid, Farid; Auriza, Moh. Zeylo (STIE Malangkucecwara, 2025)
This study aims to investigate the influence of green self-concept, altruism, and environmental knowledge on the green pruchase intention and their influence on green brand loyalty. The research uses a quantitative approach and polls 150 customers in Palu, Indonesia, who are all college educated. Online and offline questionnaires were used to gather data, which was then analyzed using Partial Least Square (PLS) to determine the correlations between variables. The findings show that environmental awareness, green self-concept, and altruism are major factors in determining green purchase intention and green brand loyalty. In addition, the link between internal characteristics. The significance of psychological and knowledge-based elements in influencing customer behavior toward eco-friendly goods is emphasized by these studies. This study contributes to the existing literature, concepts from psychology, such as altruism, self-concept, and environmental knowledge can be applied in a marketing context to influence green consumer behavior.